Exploring Antifungal Potential of Qusthul Hindi (Saussurea lappa) Root against Candida albicans: A Systematic Review - Chyntia Tresna Nastiti; Noer Halimatus Syakdiyah; Mutiara Imansari (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Candida albicans is a microflora fungal species that can be invasive in immunocompromised conditions. Challenges in its therapy include antifungal drug resistance, which encourages research to find natural ingredients to help treat fungal infections caused by Candida albicans. One of the natural ingredients empirically known to be useful as an antimicrobial is Saussurea lappa, as known as Qusthul Hindi. This study aims to review previous studies to find out the antifungal activity of this plant root extract against Candida albicans. The method used is a systematic review, by identifying, sorting, and reviewing scientific publications, particularly research articles in the specified database and time period. A few qualified scientific publications were then reviewed, and it was found that all these studies proved the antifungal activity of Saussurea lappa root extract in vitro. Saussurea lappa root provides potential to inhibit Candida albicans in vitro. However, scientific publications have not been found regarding the Saussurea lappa root extract in modulating immunity under conditions of fungal infection, nor has it been tested against Candida albicans in vivo. Therefore, further research is required to be able to utilize Saussurea lappa root in the treatment of human fungal infection.